Geração de Rastros de Mobilidade para Experimentos em Redes Veiculares* - Santana, Eduardo Felipe Zambom; Kanashiro, Lucas; Kon, Fabio (Anais do Workshop de Computação Urbana (CoUrb), 2018)
Information and Communication Technologies can improve the traffic in big cities. The deployment of vehicular networks, in which cars can communicate to each other and with the road infrastructure, is an area that is receiving a lot of attention in the last years. However, make tests and experiments in real environments are yet a challenge. This paper presents the development of a mobility trace to the city of São Paulo using InterSCSimulator, a large-scale, open-source Smart City simulator. The trace covers an area of 25 km2 and simulates more than 4 million travels (cars and buses) during a day in the city. The generated trace was tested as input in the NS-3 network simulator.